Prevalence of anemia in pregnancy and its association with birth weight - Isabel Cristina Correa Mesa; Susana Montoya Montoya; Oscar Alonso Villada Ochoa (Revista Brasileira de Saúde Materno Infantil, 2023)
Abstract Objectives: to assess the prevalence of maternal gestational anemia and its association with the birth weight. Methods: retrospective longitudinal observational study in a cohort of 370 pregnant women. Anthropometric, biochemical, ginecobstetric and sociodemographic data of both mothers and newborns were evaluated. The results of maternal erythrocyte indices were analyzed and contrasted with newborns anthropometrical data. Results: the mean age of the pregnant women was 27±6 years, with a mean gestational age of 32±6 weeks at the assessment moment, 56.2% were overweight. The prevalence of anemia was 28.6%. 47.2% women with anemia and 36% women without anemia had low birth weight/very low birth weight newborns (p=0.009). Of the children born to mothers with iron deficiency anemia, 20% had low birth weight and 15% very low birth weight. 54.3% newborns with global undernutrition or at risk of developing it were born to women with underweight(p=0.046), in addition, the higher the maternal weight, the lower the number of term newborns with risk of short height (p<0.001). Conclusions: there is relationship between the anemia, the maternal nutritional status and the birth weight.